Directional Receivers for Diffusion-Based Molecular Communications - L. Felicetti; M. Femminella; G. Reali (IEEE Access, 2019)
The particle motion in diffusion-based molecular communication systems is typically modeled by using Brownian processes. In particular, this model is used to characterize the propagation of signal molecules after their release from the transmitter. This motion cannot include directionality in the propagating signal and translates into omnidirectional broadcast communications. In order to make such molecular communications system suitable for supporting communications protocols at the molecular scales, we propose to improve the receiver capabilities by introducing a form of directionality while receiving biological signals. Inspired by the directionality introduced in electromagnetic communications by means of directional antennas, we designed a nanomachine receiver having directionality properties. Our aim is to increase the average concentration of signal molecules, also referred to as carriers, in the area around the receiver surface. In this way, it is possible to increase the signal strength at the receiver. For this purpose, we propose to use a purely reflecting shell to be placed at a configurable distance from the receiver surface. The shape of the shell can be modeled as either a spherical cap or a cylinder with an empty basis. The presence of this surface causes a number of signal molecules to remain trapped in a region close to the receiver surface for a sufficiently long time. In this way, the probability of assimilating additional carriers by the compliant receptors present on the receiver surface increases. By means of an extensive simulation campaign, we identified the most suitable configuration able to provide a significant advantage with respect to those not adopting the proposed solution. The resulting approach can be regarded as an enabler of protocols for diffusive molecular communications taking advantage of directionality properties at the receiver site. It can result in an increased communication range or in improved capabilities of discriminating signals of coexisting molecular communication systems.